A compatible carbonate electrolyte with lithium anode for high performance lithium sulfur battery. (20th August 2018) - Chen, Zhenying; Zhou, Jingjing; Guo, Yongsheng; Liang, Chengdu; Yang, Jun; Wang, Jiulin; Nuli, Yanna
Abstract: We report a new carbonate electrolyte of 1 M LiFSI dissolved in the EMC/FEC (70/30, v/v) solvent for lithium metal based batteries. Favorable LiF-rich SEI layer is formed on Li anode to suppress side reactions under the synergistic effect of LiFSI and FEC. Thus, the dendrite-free Li morphology and high Coulombic efficiency for Li plating/stripping can be obtained with improved cycle stability compared with conventional LiPF6 /EC-DMC electrolyte. Li | S@pPAN cell assembled with the new electrolyte shows quite low lithium ion transfer resistance, excellent long cycle stability and rate performance. A high discharge capacity of 1270 mAh g −1 remains after 1000 cycles at 2 C, with an inappreciable capacity decay of 0.0015% per cycle. Due to the low interface impedance and high Li + diffusion coefficient, a capacity of 1210 mAh g −1 even at 10 C can be maintained. This deliberately designed electrolyte offers new insights into the understanding of interfacial stability between electrolyte and Li anode. Furthermore, our work offers a new approach towards high energy-density and high rate Li-S battery. Graphical abstract: Exceptional performances are obtained for a Li-S@pPAN battery by using a new carbonate electrolyte based on LiFSI and FEC. Image 1 Highlights: A new carbonate electrolyte of 1 M LiFSI dissolved in EMC/FEC (70/30, v/v) is proposed for Li-based batteries. The excellent compatibility of the electrolyte with Li anode and S@pPAN cathode is revealed. LiF-rich SEI layer is formed on Li anode under the synergistic effect of LiFSI and FEC. Li-S battery using the new electrolyte demonstrates outstanding cycling stability and rate performance.